2009
DOI: 10.1111/j.1574-6941.2008.00633.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of cellulose degradation and growth of cellulolytic bacteria in the rumen

Abstract: Ruminant animals digest cellulose via a symbiotic relationship with ruminal microorganisms. Because feedstuffs only remain in the rumen for a short time, the rate of cellulose digestion must be very rapid. This speed is facilitated by rumination, a process that returns food to the mouth to be rechewed. By decreasing particle size, the cellulose surface area can be increased by up to 10(6)-fold. The amount of cellulose digested is then a function of two competing rates, namely the digestion rate (K(d)) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
118
2
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(135 citation statements)
references
References 102 publications
9
118
2
6
Order By: Relevance
“…Marinova et al (2007) suggested that changes in propionate and acetate are related to the depression of acetate-producing bacteria, which are inhibited by polyunsaturated fatty acids. However, in high-grain diets, these bacteria do not grow (Russell et al, 2009); therefore, the changes in propionate and acetate could be related to effects on the rumen protozoa, because polyunsaturated fatty acids are also toxic to rumen protozoa (Oldick and Firkins, 2000). The microbial defaunation by high-grain diets have similar effects on the fermentation pattern (Mendoza et al, 1993).…”
Section: Discussionmentioning
confidence: 83%
“…Marinova et al (2007) suggested that changes in propionate and acetate are related to the depression of acetate-producing bacteria, which are inhibited by polyunsaturated fatty acids. However, in high-grain diets, these bacteria do not grow (Russell et al, 2009); therefore, the changes in propionate and acetate could be related to effects on the rumen protozoa, because polyunsaturated fatty acids are also toxic to rumen protozoa (Oldick and Firkins, 2000). The microbial defaunation by high-grain diets have similar effects on the fermentation pattern (Mendoza et al, 1993).…”
Section: Discussionmentioning
confidence: 83%
“…Most of the work on fibre degradation in the rumen is based on three cultivable bacteria: Fibrobacter succinogenes, Ruminococcus albus and Ruminococcus flavefaciens. Because they are able to hydrolyse crystalline cellulose, they were considered to be important in the rumen (Flint et al, 2008;Wallace, 2008;Russell et al, 2009). The genomes of these three bacteria have been sequenced (see 'Rumen microbial genome projects section') and the enzymatic strategies to hydrolyse cellulose used by each species have been partially unravelled.…”
Section: The Ruminant Superorganismmentioning
confidence: 99%
“…Because cellulose is the main component of the cell wall of these plants, cellulolytic ruminal microorganisms play an important role in animal nourishment (Russell et al 2009). Cellulose is digested in the rumen (Michalet-Doreau et al 2002).…”
Section: Cellulose-degrading Bacteriamentioning
confidence: 99%